Comparative Study of Stump Closure with Knot Tying Suture Versus Metallic Endoclip in Laparoscopic Appendectomy in Uncomplicated Acute Appendicitis in Terms of Organ Injury and Intraoperative Time Taken - Raza, Muhammad Hamid; Ahmad, Bashir; Tajammal, Umer; Saeed, Muhammad Hassan; Aslam, Memoona; Ehsan, Sara; Raza, Muhammad Ahmad (Indus Journal of Bioscience Research, 2025)
Introduction: Endoloops (EL), endoclips (both metallic and polymeric clips), linear stapler devices, suture closure via additional—corporeal sliding knots, or intracorporeal knot ligation and endocoagulation are some of the several laparoscopic closure techniques for the appendiceal stump that have been previously described. However, opinions on the best way to close appendiceal stumps are divided. Study design: Randomized controlled trial. Study Period: July 25, 2024, until January 24, 2025. Methodology: There were 300 patients between the ages of 18 and 70 years, regardless of gender, who have undergone laparoscopic appendiceal stump closure due to uncomplicated acute appendicitis were included. The following conditions were not included: conversion to open appendectomy, single incision appendectomy, diffuse or local peritonitis, inflammatory pelvic illness, and the use of alternative stump closure procedures. Group A patients were undergone metallic endo-clip and group B patients were undergone knot tying. Operative time and intra-operative organ injury were assessed. Findings: Group A (metallic clip) in my study had an average surgery time of 37.87 ± 6.52 minutes, while Group B (knot tying) had an average surgery time of 49.87 ± 4.52 minutes (p-value = 0.0001). 2.67% of patients in group A (met6allic clip) experienced organ injury, whereas 0.67% of patients in group B (knot tying) did the same. Conclusion: For patients with complex appendicitis, there are safe alternatives for appendiceal stump closure during laparoscopic appendectomy: metallic endoclips and intracorporeal sutures.